Three-dimensional distribution of the UV-inducible blue-green fluorescence in leaves - Hideg, Éva (Acta Biologica Szegediensis, 2002)
Ultraviolet (UV. 290-360 nm) excitation provokes 400-560 nm intrinsic light emission from a vast majority of plant leaves. Using confocal laser scanning microscopy, we show in this study that blue-green fluorescence (BGF) mainly originates in the epidermal surface of Sorghum vulgare leaves. BGF was also detected from the cell walls and stomata guard cells. Our experiments support earlier suggestions on the heterogeneous nature of BGF fluorophores.